Cercyon (Cercyon) symbion Shatrovskiy 1989 ... - Sazhnev, A. S.; Prokin, A. A.; Sergeev, M. E. (Zenodo, 2021)
Cercyon (Cercyon) symbion Shatrovskiy, 1989 MATERIAL EXAMINED. 3: 1.VI.2018, 1 ex.; 4: 5.VII.2019, 1 ex. DISTRIBUTION. Russian Far East (Commander Islands, Kuril Islands, Primorsky Krai, Sakhalin, Isl.), Japan [Shatrovskiy, 1989b, 1992; Prokin, 2009; Fikáček et al., 2015; Sazhnev, 2018]. ... : Published as part of Sazhnev, A. S., Prokin, A. A. & Sergeev, M. E., 2021, New data on water beetles (Coleoptera: Gyrinidae, Haliplidae, Noteridae, Dytiscidae, Hydrophilidae, Elmidae) of Primorsky Krai (Russia), pp. 264-274 in Russian Entomological Journal 30 (3) on page 268, DOI: 10.15298/rusentj.30.3.03, http://zenodo.org/record/13178748 ...